The use of history to identify anterior cruciate ligament injuries in the acute trauma setting: the 'LIMP index'. Issue 5 (31st January 2017) - Ayre, Colin; Hardy, Maryann; Scally, Andrew; Radcliffe, Graham; Venkatesh, Ram; Smith, Jon; Guy, Stephen
Abstract : Objective: To identify the injury history features reported by patients with anterior cruciate ligament (ACL) injuries and determine whether history may be used to identify patients requiring follow-up appointments from acute trauma services. Methods: Multisite cross-sectional service evaluation using a survey questionnaire design conducted in the UK. The four injury history features investigated were 'leg giving way at the time of injury', 'inability to continue activity immediately following injury', 'marked effusion' and 'pop (heard or felt) at the time of injury'(LIMP). Results: 194 patients with ACL injury were identified, of which 165 (85.5%) attended an acute trauma service. Data on delay was available for 163 (98.8%) of these patients of which 120 (73.6%) had a follow-up appointment arranged. Patients who had a follow-up appointment arranged waited significantly less time for a correct diagnosis (geometric mean 29 vs 198 days; p<0.001) and to see a specialist consultant (geometric mean 61 vs 328 days; p<0.001). Using a referral threshold of any two of the four LIMP injury history features investigated, 95.8% of patients would have had a follow-up appointment arranged. Conclusions: Findings support the value of questioning patients on specific injury history features in identifying patients who may have suffered ACL injury. Using a threshold of two or more of the four LIMP history features investigated would have reduced the percentage of patients inappropriately discharged by 22.2%. Evidence presented suggests that this would significantly reduce the time to diagnosis and specialist consultation minimising the chance of secondary complications.